PEMBERIAN AIR KELAPA MUDA UNTUK PENURUNAN NYERI HAID PADA STAF PUSKESMAS HUTABARGOT MANDAILING NATAL - Herri Novita Tarigan; Megawati Sinambela (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Dismenorhoe is a medical condition that occurs to menstruation that can interfere with activity and requires treatment characterized by pain or pain in the abdomen or pelvis . Menstruation is periodic bleeding and cycles from the uterus , accompanied by the release or dedeconstruction of the endometrium that occurs every month regularly in mature and healthy women . The purpose of this study is to find out if there is an " Giving of Young Coconut Water On Decreased Dismenorhoe This type of research uses pre experimental methods and design of one group pretest-Postest .The sample numbered 10 respondents with the same treatment. With Numerical pain measurement scale and Observation Sheet . Univariate and Bivariate analysis using t analysis. The results of this study obtained the results of Pretest 7.40 and Posttest 2.8. So it can be concluded that " there is an effect of young coconut water administration on menstrual pain after and before intervention .